Imaginaire du corps enseignant au cinéma et corps imaginé par l’enseignant en formation : quelles interactions ? - Mandarine Hugon; Christine Ramat (Mise au Point)
The educational relationship involving the teacher’s body and voice is linked to the professional’s representations of his or her profession and of his or her students. What representations do trainee teachers have of their ‘professional body’ on the educational stage? Can the cinema be a tool to encourage awareness of the role of the body and the voice in teaching? What then of the imaginary of the teaching profession and its representations in contemporary cinema? The school is a favourite subject for the cinema and the figure of the teacher an inexhaustible source of inspiration for fiction, so much so that since the 1960s there have been hundreds of films on the subject and several studies on the image of teachers in the media (Legrand et Kovacs Bosch, 1995; Maulini, 2011; Bonneau, 2015). How are teacher-pupil physical interactions portrayed? In order to compare the imaginary bodies of teachers in training with those depicted on screen, we have observed the way in which teachers’ and pupils’ bodies are represented, based on analyses of training situations and extracts from films known to the general public. The results of our study make it possible to analyse the cultural representations of a professional body and to consider, in initial teacher training (Jourdan, 2014; Tellier & Yerian, 2018), the devices for ‘bringing the body into play’ in the practice of trainee teachers.